EFFECTS OF DIGITAL GAME-BASED LEARNING ON PRODUCT INNOVATION SKILLS DEVELOPMENT: COMPARATIVE ANALYSIS BETWEEN APPLIED ARTS AND APPLIED SCIENCE UNDERGRADUATE STUDENTS - Tan Bee Sian; Tan Wee Hoe; Ahmad Zamzuri Mohammad Ali; Chong Kim Soon (UUM Press, 2024)
Purpose - This study investigates how Digital Game-based Learning (DGBL) impacts the development of product innovation skills among undergraduate students, comparing the performance of students across different disciplines-Applied Arts (AA) and Applied Sciences (AS).  Methodology - The study involved 80 undergraduate students: 40 students pursuing an AA degree and 40 pursuing an AS degree. The design of the innovation game incorporated cognitivist learning strategies based on Bloom's taxonomy. Innovation skills were evaluated through an open-ended achievement test.  Findings - The study revealed that DGBL effectively enhances product innovation skills by integrating cognitive strategies, and Bloom's Taxonomy into guided answers, and open-ended achievement tests. AS students excelled in problem identification and idea creation, while AA students emphasised psychological, emotional factors and visualisation representation.  Significance - The findings suggest promoting interdisciplinary collaboration among educators and policymakers to integrate aesthetics and technological knowledge. This approach enables students from diverse disciplines to leverage their strengths for holistic innovation. For practical applications, game designers and educators can model product innovation steps, offer guided answers, track progress and award virtual badges. The open-ended achievement test is a valuable tool for assessing innovation skills across diverse student backgrounds. Future studies should focus on integrating cognitivism and constructivism in collaborative learning, using generative AIassisted assessment, and bridging virtual idea generation with real-world product idea pitching using voice-input technologies. In conclusion, this study provides practical guidelines for implementing DGBL in product innovation, influencing education, policy-making, and design practices.